ANALISIS PERSEPSI KONSUMEN MUSLIM TERHADAP OBAT- OBATAN HALAL DALAM KAITANNYA DENGAN IMPLEMENTASI UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Salsabila Permatasari Putri Nugroho (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
Basically, a Muslim is obligated to consume something Halal and stay away from Haram, for example, consumption of food, drink, medicine, etc. However, in practice, Muslim consumer only focus on Halal food and drinks, and forgot things that are equally important, which is medicines. This study aims to analyze and examine the effect of Halal knowledge, Halal awareness, and attitude, on people’s perception of Halal medicines. This study uses data collection through questionnaires, it takes a sample of 100 respondens with the following criteria; respondents are Muslim, and have purchased medicines both over-the-counter or with a doctor’s prescription within the last 3 months. The results of this study indicate that Halal knowledge and attitude have a positive effect on people’s perception of Halal medicines, while Halal awareness is stated have no effect on consumer’s perception of Halal medicines.